Nursing care to patients with stroke: an integrative review - Bianchini, Suzana Maria; Galvão, Cristina Maria; Arcuri, Edna Apparecida Moura (Online Brazilian Journal of Nursing, 2010)
Stroke is the most frequent cause of death in Brazil, being more impairing than lethal. Treatment must be quick; the thrombolysis therapeutic window for the ischemic subtype (87% of cases) is within three hours. This integrative review has analyzed nursing care knowledge available for the acute phase of stroke. Searches (LILACS, MEDLINE e CINAHL) resulted in ten studies divided into four categories and analyzed under referral patterns with seven levels of evidence. Analysis has shown poor levels of evidence. However, important aspects of blood pressure, oxygen saturation, blood glucose, position of head section, thrombolytic, neurological evaluation scales and nursing care result indicators have been analyzed. Knowledge in the area stimulates reflection on the creation of stroke units with skilled, trained professionals, besides investment in continuing education. Research with better levels of evidence could help nurses meet these targets.